Integrated structure composite conduction type solid oxide battery and preparation method thereof

By limiting the ratio and particle size of proton conductor materials and oxygen ion conductor materials, more conduction paths were prepared, which solved the problem of insufficient stability of H-SOFC at high temperatures and achieved higher fuel cell work Efficiency and adaptability.

CN119419321AActive Publication Date: 2025-02-11NORTH CHINA ELECTRIC POWER UNIV

Patent Information

Application Number
CN202411578842.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-11
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing proton conductor solid oxide fuel cells (H-SOFCs) have insufficient chemical and mechanical stability at high temperatures, resulting in the possible degradation in long-term operation.

Method used

By defining the ratio and particle size of the proton conductor material and the oxygen ion conductor material, more conduction paths are prepared to increase the output power of the solid oxide battery. The specific method includes setting the molar ratio of the proton conductor material and the oxygen ion conductor material to 1: (0.8 to 1.2), and preparing an integrated skeleton by thermal isostatic pressure and sintering process.

Benefits of technology

The fusion of oxygen ion conduction and proton conduction is achieved, the range of ion transmission channels is expanded, and the working efficiency and adaptability of fuel cells is significantly improved, so that the battery can operate efficiently in a wider temperature range, and the material is improved. Sintering properties and mechanical strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119419321A_ABST
    Figure CN119419321A_ABST
Patent Text Reader

Abstract

The present invention provides an integrated structure composite conduction type solid oxide cell and a preparation method thereof, and belongs to the technical field of solid oxide fuel cells, the integrated structure composite conduction type solid oxide cell comprises: an integrated skeleton, the integrated skeleton comprises an electrolyte layer and porous layers on two sides, the integrated skeleton is composed of a proton conductor material and an oxygen ion conductor material, the molar ratio of the proton conductor material to the oxygen ion conductor material is 1: (0.8-1.2), and the proton / oxygen ion composite material is prepared by mixing and sintering the proton conductor material with the average particle size of 50-60 nm and the oxygen ion conductor material with the average particle size of 0.1-0.2 [mu] m; the catalyst layer is positioned on the pore wall of the porous layer. According to the invention, by limiting the proportion and the particle size of the proton conductor material and the oxygen ion conductor material, more conduction type paths are prepared, and the output power of the solid oxide battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid oxide fuel cells, and in particular relates to an integrated structure composite conductive solid oxide battery and a preparation method thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) is a clean energy conversion device that can directly convert chemical energy into electrical energy. According to the different ions conducted by the electrolyte material, SOFC can be divided into oxygen ion conductor type (O-SOFC) and proton conductor type (H-SOFC). Traditional high-temperature O-SOFC has been developed for many years, with mature preparation technology and excellent performance at high temperatures. However, as the working conditions of the battery develop towards medium and low temperatures, proton conductor SOFC (H-SOFC) has received widespread attention due to its lower operating temperature, smaller activation energy value and higher battery efficiency. However, H-SOFC is not yet mature, and the chemical stability and mechanical stability of proton conductor materials at high temperatures still need to be further improved to ensure that they do not degrade during long-term operation.

[0003] Prior art: A Chinese invention patent with announcement number CN109921079B discloses a composite solid oxide fuel cell and a preparation method thereof. The composite electrolyte layer has both proton conductivity and oxygen ion conductivity. The electrolyte ion conductivity can meet the performance requirements at medium, low and high temperatures. The composite porous electrolyte separator can effectively block the reaction between the cathode and the electrolyte, reduce the interface resistance, and the double cathode layer is composed of an electronic conductivity enhancement layer and an ion conductivity enhancement layer, which greatly reduces the polarization resistance. The invention patent with announcement number CN114843569B discloses a proton-oxygen ion mixed conductor electrolyte preparation method, product and battery. SDC is introduced into BZCYYb and evenly distributed to prepare a proton-dominated proton-oxygen ion mixed conductor electrolyte and anode, reduce the sintering temperature, and can conduct a small amount of oxygen ions to the anode and react to generate a certain amount of water vapor, realize in-situ humidification of the anode, and ultimately reduce production and operation costs. However, the above technical solution has corresponding problems. Since the electrolyte is prepared by mixing proton conductor materials and oxygen ion conductor materials, if the mixing uniformity is high, similar to an amorphous structure, the proton conductive pathway and the oxygen ion conductive pathway in the electrolyte cannot connect the two sides of the electrolyte, which will reduce the performance of the prepared solid oxide battery. If the mixing degree is poor, a large proportion of non-conductive pathways will appear, which will also reduce the performance of the prepared solid oxide battery. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present invention provides an integrated structure composite conductive solid oxide battery and a preparation method thereof. By limiting the ratio and particle size of the proton conductor material and the oxygen ion conductor material, more conductive pathways are prepared, thereby improving the output power of the solid oxide battery.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] On the one hand, the present invention provides an integrated structure composite conductive solid oxide battery, comprising: an integrated skeleton, the integrated skeleton comprising an electrolyte layer and porous layers on both sides, the integrated skeleton is composed of a proton conductor material and an oxygen ion conductor material, the molar ratio of the proton conductor material to the oxygen ion conductor material is 1:(0.8-1.2), and is prepared by mixing and sintering a proton conductor material with an average particle size of 50-60nm and an oxygen ion conductor material with an average particle size of 0.1-0.2μm; a catalyst layer, the catalyst layer is located on the pore wall of the porous layer.

[0007] Furthermore, the electrolyte layer and the porous layer use the same proton conductor material and oxygen ion conductor material and the molar ratio of the two is the same.

[0008] Furthermore, the proton conductor material includes: BaZr 1-x Y x O 3-δ 、BaZr 1-x Yb x O 3-δ 、BaZr 1-x- y Ce y Y x O 3-δ 、BaZr 1-x-y-z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。

[0009] Furthermore, the oxygen ion conductor material includes: Zr x Y y O 2-δ 、Ce x Sm y O 2-δ , Ce x G y O 2-δ ,La 1- x Sr x Ga 1-y Mg yO 3-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。

[0010] On the other hand, the present invention provides a method for preparing the above-mentioned solid oxide battery, comprising: preparing an integrated skeleton; and preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0011] Furthermore, preparing the integrated skeleton includes: preparing an electrolyte membrane and two electrode membranes; forming the integrated skeleton green body by hot isostatic pressing according to "electrode membrane|electrolyte membrane|electrode membrane"; and sintering the integrated skeleton green body to obtain the integrated skeleton.

[0012] Furthermore, the preparation method of the slurry of the electrolyte membrane and the electrode membrane is: weigh and mix the proton conductor material and the oxygen ion conductor material according to a preset ratio, add 8%-13% of the total powder mass of a dispersant, 3%-7% of the total powder mass of a plasticizer and 9%-12% of the total powder mass of a binder and mix well.

[0013] Furthermore, the dispersant is one or more of triethanolamine, sodium polyacrylate and polyoxyethylene; the plasticizer and binder are one or more of dioctyl phthalate, polyethylene glycol, polyvinyl alcohol and polyvinyl acetate.

[0014] Furthermore, the hot isostatic pressing process is: maintaining at 50-85°C and a pressure of 10-60MPa for at least 30 minutes.

[0015] Furthermore, the sintering process is: raising the temperature to 650-700°C at a rate of no more than 1°C / min and keeping the temperature for at least 30 minutes, raising the temperature to 1200-1600°C at a rate of no more than 3°C / min and keeping the temperature for 2-20 hours, and then reducing the temperature to room temperature at a rate of no more than 5°C / min.

[0016] Compared with the prior art, the technical solution provided by the present invention brings the following beneficial effects:

[0017] (1) The present application defines the average particle size and addition amount of the proton conductor material and the oxygen ion conductor material. The average particle size and addition amount of the proton conductor material and the oxygen ion conductor material determine the distribution characteristics between the two. Specifically, the particle size of the proton conductor material is relatively small, which is suitable for the transfer of H ions. Moreover, due to the small particle size, high surface free energy and strong adsorption capacity of the proton conductor material, it can form certain agglomerates attached to the surface of the agglomerated block formed by the oxygen ion conductor material, and form a passage after sintering. However, the particle size of the proton conductor material should not be too small. If it is too small, it will agglomerate itself severely and cannot be sintered to form an effective conductive passage. The larger particle size of the oxygen ion conductor material is considered that the oxygen ion conductor material should not form spherical agglomerates, but heterogeneous agglomerates, thereby increasing the probability of the oxygen ion conductor material penetrating the passages on both sides of the electrolyte. Secondly, The formation of the above-mentioned pathway is closely related to the ratio of the proton conductor material and the oxygen ion conductor material, especially the proton conductor material. If the molar ratio is small, it may not be possible to form an effective conductive pathway, but instead lead to a decrease in power; while if the molar ratio is high, the ratio of the oxygen ion conductor material is reduced, resulting in the oxygen ion conductor material being easily formed into spherical agglomerates, reducing the effective conductive pathway of the oxygen ion channel; finally, the particle size and ratio of the above-mentioned proton conductor material and oxygen ion conductor material can reduce the probability of cracks caused by the difference in thermal properties between the two. Since the integrated skeleton is prepared by using two materials and the selection range of the two materials is large, it is necessary to consider the difference in thermal properties between different materials. In this application, by limiting the particle size and ratio of the proton conductor material and the oxygen ion conductor material, the influence of the difference in thermal properties on the prepared integrated skeleton can be ignored.

[0018] (2) The overall skeleton region of the integrated structure proton oxygen ion composite conduction solid oxide battery realizes the fusion of oxygen ion conduction and proton conduction fuel cells, and the range of ion transmission channels is wider. This fusion significantly improves the working efficiency and adaptability of the fuel cell, enabling the battery to operate efficiently within a wider temperature range, fully utilizing the advantages of different working conditions and achieving higher fuel utilization.

[0019] (3) The composite conductor material is composed of nano-sized proton conductor material and micron-sized oxygen ion conductor material, and 1% by mass NiO is added to the proton conductor material as a sintering aid. By using material particles of different particle sizes, the sintering performance of the material is significantly improved, and the mechanical strength and durability of the material are enhanced to a certain extent.

[0020] (4) The main skeleton support structure of the integrated proton-oxygen ion composite conductive solid oxide battery is a whole: this overall structure ensures the close combination of the electrode and the electrolyte layer, effectively avoids the separation problem that may occur during operation, and enhances the stability and durability of the battery.

[0021] (5) The electrode material is impregnated into the porous skeleton surface through an impregnation process to construct a nanostructured electrode: The nanostructured electrode is located on the skeleton surface, which greatly increases the reaction active sites and does not occupy the composite conductor area. The connectivity of each phase in the skeleton is better, which not only maintains the high activity of the catalyst and increases the electrode reaction rate, but also ensures that the composite conductor ceramic skeleton has good proton and oxygen ion conductivity, further improving the overall performance of the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 A schematic diagram of a solid oxide battery provided by an embodiment of the present invention;

[0024] Figure 2 A schematic diagram of a non-conductive path of a solid oxide battery provided by an embodiment of the present invention;

[0025] Figure 3 This is a SEM image of the solid oxide battery provided in Example 1 of the present invention;

[0026] Figure 4 This is a partially enlarged view of the solid oxide battery provided in Example 1 of the present invention.

[0027] Figure numerals: 1. oxygen electrode catalyst layer; 2. integrated skeleton; 3. fuel electrode catalyst layer. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The specific implementation of the present invention is not limited to the specific embodiments given here, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the disclosed specific embodiments.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used are only for describing specific embodiments and do not limit the present invention.

[0030] The embodiment of the present invention provides an integrated structure composite conductive solid oxide battery, such as Figure 1As shown, it includes: an integrated skeleton 2, the integrated skeleton 2 includes an electrolyte layer and porous layers on both sides, the integrated skeleton 2 is composed of a proton conductor material and an oxygen ion conductor material, the molar ratio of the proton conductor material to the oxygen ion conductor material is 1: (0.8-1.2), and is prepared by mixing and sintering a proton conductor material with an average particle size of 50-60nm and an oxygen ion conductor material with an average particle size of 0.1-0.2μm; a catalyst layer, the catalyst layer is located on the pore wall of the porous layer. Figure 1 As shown, the catalyst layer includes an oxygen electrode catalyst layer 1 and a fuel electrode catalyst layer 3 .

[0031] In the prior art, such as Figure 2 As shown, the composite conductive integrated skeleton includes proton conductor materials and oxygen ion conductor materials. The proton conductor materials are used to transport protons, and the oxygen ion conductor materials are used to transport oxygen ions. The prepared integrated skeleton inevitably has non-conductive pathways, and the non-conductive pathways reduce the interface area for proton or oxygen ion transmission, resulting in lower power. In order to solve the above problems, the present application defines the average particle size and addition amount of the proton conductor material and the oxygen ion conductor material, and the average particle size and addition amount of the proton conductor material and the oxygen ion conductor material determine the distribution characteristics between the two. Specifically, the particle size of the proton conductor material is relatively small, which is suitable for the transfer of H ions. Moreover, since the proton conductor material has a small particle size, high surface free energy, and strong adsorption capacity, it can form certain agglomerates attached to the surface of the agglomerated block formed by the oxygen ion conductor material, and form a passage after sintering. However, the particle size of the proton conductor material should not be too small. If it is too small, it will agglomerate severely and cannot be sintered to form an effective conductive passage. The larger particle size of the oxygen ion conductor material is set to take into account that the oxygen ion conductor material should not form spherical agglomerates, but heterogeneous agglomerates, thereby increasing the probability of the oxygen ion conductor material penetrating the passages on both sides of the electrolyte. Secondly, the formation of the above-mentioned pathway is closely related to the ratio of the proton conductor material and the oxygen ion conductor material, especially the proton conductor material. If the molar ratio is small, it may not be possible to form an effective conductive pathway, but instead lead to a decrease in power; while if the molar ratio is high, the ratio of the oxygen ion conductor material is reduced, resulting in the oxygen ion conductor material being easily formed into spherical agglomerates, reducing the effective conductive pathway of the oxygen ion channel; finally, the particle size and ratio of the above-mentioned proton conductor material and oxygen ion conductor material can reduce the probability of cracks caused by the difference in thermal properties between the two. Since the integrated skeleton is prepared by using two materials and the selection range of the two materials is large, it is necessary to consider the difference in thermal properties between different materials. The present application limits the particle size and ratio of the proton conductor material and the oxygen ion conductor material, and can ignore the influence of the difference in thermal properties on the prepared integrated skeleton.

[0032] Specifically, the electrolyte layer and the porous layer use the same proton conductor material and oxygen ion conductor material and the molar ratio of the two is the same, so as to improve the coordination between the electrolyte layer and the porous layer during the heating and cooling process, and avoid stress at the interface between the porous layer and the electrolyte layer due to different thermal properties. When the stress is greater than the local maximum allowable stress, cracks will appear, causing the performance of the solid oxide battery to decay.

[0033] Specifically, the proton conductor material includes: BaZr 1-x Y x O 3-δ 、BaZr 1-x Yb x 、BaZr 1-x-y Ce y Y x O 3-δ 、BaZr 1-x-y-z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。

[0034] Specifically, the oxygen ion conductor material includes: ZrO 2-x Y2O 3-δ 、Ce x Sm y O 2-δ 、Ce x G y O 2-δ ,La 1- x Sr x Ga 1-y Mg y O 3-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。

[0035] Specifically, the oxygen electrode catalyst layer is composed of an electronic conductor or a mixed conductor of ions and electrons, and the specific materials include: Pr6O 11 、Ce 1-x Pr x O2、PrNi 1-x Co x O 3-δ , Ba 1-x Sr x Co y Fe 1-y O 3-δ ,La 1-x Sr x Co y Fe 1-y O3-δ 、BaCo y Fe 1-x-y-z Zr x Y z O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。

[0036] Specifically, the fuel electrode catalyst layer is composed of metal or metal ceramic composite material or electronic ion mixed conductor, and the specific materials include: Ni, NiFe, Ni / Ce 1-x G x O 2-δ 、Ni / Sm 1-x Ce x O 2-δ 、Sr2Fe 2-x Mo x O 6-δ One or more of, where 0 <x<1,0<δ<1。

[0037] For illustration purposes, the proton conductor material in the subsequent embodiments is BaZr. 0.7 Ce 0.2 Y 0.1 O 3-δ and BaZr 0.7 Ce 0.1 Y 0.1 Yb 0.1 O 3-δ The oxygen ion conductor material is GDC and SDC, where GDC is CeO2 stabilized by Gd2O3 with a molar composition of 40%, and SDC is Sm 0.2 Ce 0.8 O2, Ni / SDC is used as the fuel electrode catalyst, and PrNi is used as the oxygen electrode catalyst 0.5 Co 0.5 O 3-δ or La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ .

[0038] The solid oxide battery prepared by the present invention has a porosity of 10%-60% on the oxygen electrode side, a structural density of the composite conductor electrolyte layer of not less than 95%, and a porosity of 10%-60% on the fuel electrode side. The thickness of the integrated structure of proton-oxygen ion composite conduction prepared in the embodiment of the present invention is 200-1500 μm, wherein, according to the different supporting structures, these structures can be further divided into electrolyte-supported and electrode-supported types, the thickness of the oxygen electrode is 10-50 μm, the thickness of the composite conductor electrolyte layer is 10-700 μm, and the thickness of the fuel electrode is 10-700 μm. The thickness of the prepared fuel electrode catalyst layer and oxygen electrode catalyst layer is 50-200 nm.

[0039] The present invention also provides a method for preparing the solid oxide battery, comprising:

[0040] S1. Prepare an integrated skeleton.

[0041] The preparation of the integrated skeleton includes:

[0042] S10 prepares an electrolyte membrane and two electrode membranes;

[0043] The preparation method of the slurry of the electrolyte membrane and the electrode membrane is:

[0044] According to the preset ratio, the proton conductor material and the oxygen ion conductor material are weighed and mixed, and 8%-13% of the total powder mass of the dispersant, 3%-7% of the total powder mass of the plasticizer and 9%-12% of the total powder mass of the binder are added and mixed. As the second technical difficulty of this application, how to ensure that the slurry prepared by the proton conductor material or the oxygen ion conductor material has a certain dispersibility and a certain agglomeration. The reason why a certain dispersibility needs to be maintained is that on the one hand, large-area agglomeration between powders is avoided, resulting in cracks due to large differences in thermal properties during the preparation of the integrated skeleton. On the other hand, if the dispersibility is too high, an amorphous structure similar to that will appear, and an effective conductive path cannot be formed, but the power of the solid oxide battery is reduced. Therefore, it is necessary to limit the content of the dispersant, plasticizer and binder to ensure that the prepared slurry has appropriate dispersibility and agglomeration, so as to prepare an integrated skeleton with many conductive paths.

[0045] Specifically, the dispersant is one or more of triethanolamine, sodium polyacrylate and polyoxyethylene; the plasticizer and binder are one or more of dioctyl phthalate, polyethylene glycol, polyvinyl alcohol and polyvinyl acetate, all of which are commercially available products. Since the plasticizer can usually also be used as a binder, the plasticizer and the binder can be the same or different from the above substances.

[0046] Sodium polyacrylate was purchased from Zhonglian Federation, model K-334; polyoxyethylene used WSR N-10NF grade; polyethylene glycol used polyethylene glycol 1500; polyvinyl alcohol used polyvinyl alcohol 1750±50; polyvinyl acetate was purchased from Thermo Fisher, catalog number 18326.

[0047] The preparation methods of the electrolyte membrane and the electrode membrane include: one or more of tape casting, screen printing, spin coating, and spray coating. For the purpose of illustration, the following embodiments are described using the tape casting method.

[0048] It should be pointed out that the above-mentioned mixing or blending is carried out by ball milling, and the ball milling time is not less than 36 hours.

[0049] S11 is formed by hot isostatic pressing according to "electrode membrane | electrolyte membrane | electrode membrane" to obtain an integrated skeleton green body.

[0050] The process of hot isostatic pressing is: keep at 50-85℃ and 10-60MPa pressure for at least 30min. Multi-step hot isostatic pressing is to add different membranes layer by layer and perform hot isostatic pressing. For example, the fuel electrode membrane and the electrolyte membrane are first hot isostatically pressed. After the completion, the oxygen electrode membrane is stacked on the other side of the electrolyte membrane and hot isostatically pressed. After the hot isostatic pressing is completed, an integrated skeleton green body is obtained.

[0051] S12 sintering the integrated skeleton green body to obtain the integrated skeleton.

[0052] The sintering process is: heating to 650-700°C at a rate of no more than 1°C / min and keeping the temperature for at least 30 minutes, heating to 1200-1600°C at a rate of no more than 3°C / min and keeping the temperature for 2-20 hours, and then cooling to room temperature at a rate of no more than 5°C / min. The sintering process of the present application fully considers the different thermal properties of the proton conductor material and the oxygen ion conductor material to avoid cracks between the two phases during the sintering process.

[0053] S2. Preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0054] The catalyst layer is prepared on the inner wall of the porous layer of the integrated skeleton. The catalyst layer can be prepared by impregnation or hydrothermal reaction. The embodiment of the present invention preferably adopts the impregnation method to prepare the catalyst layer, and then high-temperature sintering is used to prepare the solid oxide battery.

[0055] The high temperature sintering process is: sintering at a temperature of 700-1000° C. for 1.5-3.0 hours.

[0056] The working conditions for testing the battery performance in the embodiment of the present invention are: using high-purity H2 as the fuel gas with a flow rate of 75 mL / min, air as the oxidant with a flow rate of 150 mL / min, and measuring the open circuit voltage and power at 500°C.

[0057] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0058] Example 1

[0059] This embodiment provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, comprising:

[0060] S1. Prepare an integrated skeleton.

[0061] In BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ 1% by mass of NiO sintering aid was added to the powder, and after being evenly mixed by ball milling, it was mixed with GDC powder in a molar ratio of 1:1. 0.7 Ce 0.2 Y 0.1 O 3-δ The average particle size of the powder is 50nm, and the average particle size of the GDC powder is 0.1μm. 10% of the total powder mass of triethanolamine, 5% of the total powder mass of dioctyl phthalate and 10% of the total powder mass of polyethylene glycol are added to prepare an electrolyte casting slurry, and zirconium oxide ball milling beads are added for ball milling for 36 hours to obtain the electrolyte casting slurry; the same method and materials are used to prepare an electrode skeleton casting slurry containing 40% pore-forming agent; a membrane belt casting machine is used to prepare two electrode membranes and an electrolyte casting membrane; hot isostatic pressing is used to form "electrode membrane|electrolyte membrane|electrode membrane" to obtain an integrated skeleton green body; the integrated skeleton green body is sintered, and the sintering process is: heating to 650℃ at 0.5℃ / min and keeping for 30min, heating to 1400℃ at 3℃ / min and keeping for 10h, and then cooling to room temperature at 3℃ / min to obtain the integrated skeleton.

[0062] S2. Preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0063] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0064] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0065] The impregnation solution is taken and dripped into the electrode skeleton of the corresponding functional area, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally sintering is performed to obtain a complete solid oxide battery. The sintering process is: sintering at a temperature of 800°C for 2h. The prepared solid oxide battery is as follows Figure 3 shown.

[0066] from Figure 4 It can be seen that the solid oxide battery prepared in this application has more conductive paths and no cracks are found. Through measurement, the open circuit voltage is 1.005V and the power can reach 601mW·cm -2 .

[0067] Example 2

[0068] This embodiment provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, comprising:

[0069] S1. Prepare an integrated skeleton.

[0070] In BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ 1% by mass of NiO sintering aid was added to the powder, and after being evenly mixed by ball milling, it was mixed with GDC powder in a molar ratio of 1:0.8. 0.7 Ce 0.2 Y 0.1 O 3-δThe average particle size of the powder is 55nm, and the average particle size of the GDC powder is 0.13μm. 8% of the total powder mass of triethanolamine, 3% of the total powder mass of dioctyl phthalate and 9% of the total powder mass of polyethylene glycol are added to prepare an electrolyte casting slurry, and zirconium oxide ball milling beads are added for ball milling for 36 hours to obtain the electrolyte casting slurry; the same method and materials are used to prepare an electrode skeleton casting slurry containing 40% of a pore-forming agent; a membrane belt casting machine is used to prepare two electrode membranes and an electrolyte casting membrane; hot isostatic pressing is used to form "electrode membrane|electrolyte membrane|electrode membrane" to obtain an integrated skeleton green body; the integrated skeleton green body is sintered, and the sintering process is: heating to 700°C at 1°C / min and keeping for 30min, heating to 1200°C at 3°C / min and keeping for 2h, and then cooling to room temperature at 5°C / min to obtain the integrated skeleton.

[0071] S2. Preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0072] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0073] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0074] The above impregnation solution was absorbed and dripped into the electrode skeleton of the corresponding functional area, and then placed in a muffle furnace for debinding treatment. The above operation was repeated many times until the solution could no longer penetrate, and finally sintered to obtain a complete solid oxide battery. The sintering process was: sintering at 700°C for 1.5h.

[0075] The solid oxide battery prepared in this application has more conductive paths and no cracks are found; through measurement, the open circuit voltage of the prepared solid oxide battery is 1.001V, and the power can reach 588mW·cm -2 .

[0076] Example 3

[0077] This embodiment provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, comprising:

[0078] S1. Prepare an integrated skeleton.

[0079] In BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ 1% by mass of NiO sintering aid was added to the powder, and after being evenly mixed by ball milling, it was mixed with GDC powder in a molar ratio of 1:1.2. 0.7 Ce 0.2 Y 0.1 O 3-δ The average particle size of the powder is 60nm, and the average particle size of the GDC powder is 0.2μm. 13% of the total powder mass of triethanolamine, 7% of the total powder mass of dioctyl phthalate and 12% of the total powder mass of polyethylene glycol are added to prepare an electrolyte casting slurry, and zirconium oxide ball milling beads are added for ball milling for 36 hours to obtain the electrolyte casting slurry; the same method and materials are used to prepare an electrode skeleton casting slurry containing 40% of a pore-forming agent; a membrane belt type casting machine is used to prepare two electrode membranes and an electrolyte casting membrane; hot isostatic pressing is used to form "electrode membrane|electrolyte membrane|electrode membrane" to obtain an integrated skeleton green body; the integrated skeleton green body is sintered, and the sintering process is: heating to 650°C at 0.5°C / min and keeping for 1h, heating to 1600°C at 3°C / min and keeping for 20h, and then cooling to room temperature at 5°C / min to obtain the integrated skeleton.

[0080] S2. Preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0081] According to the molar ratio of Pr:Ni:Co=2:1:1, metal nitrates Pr(NO3)3, Ni(NO3)3, and Co(NO3)2 were mixed, and then a surfactant was added at 10% of the total mass of the added Pr, Ni, and Co elements, and a certain amount of water was added to prepare a PNC oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0082] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0083] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally sintering is performed to obtain a complete solid oxide battery. The sintering process is: sintering at a temperature of 1000°C for 3 hours.

[0084] The solid oxide battery prepared in this application has more conductive paths and no cracks are found; through measurement, the open circuit voltage of the prepared solid oxide battery is 1.003V, and the power can reach 594mW·cm -2 .

[0085] Example 4

[0086] This embodiment provides a method for preparing a solid oxide battery, and a solid oxide battery prepared by the method, comprising:

[0087] S1. Prepare an integrated skeleton.

[0088] In BaZr 0.7 Ce 0.1 Y 0.1 Yb 0.1 O 3-δ 1% by mass of NiO sintering aid was added to the powder, and after being evenly mixed by ball milling, it was mixed with SDC powder in a molar ratio of 1:1. 0.7 Ce 0.1 Y 0.1 Yb 0.1 O 3-δ The average particle size of the powder is 50nm, and the average particle size of the SDC powder is 0.1μm. 10% of the total powder mass of triethanolamine, 5% of the total powder mass of dioctyl phthalate and 10% of the total powder mass of polyethylene glycol are added to prepare an electrolyte casting slurry, and zirconium oxide ball milling beads are added for ball milling for 36 hours to obtain the electrolyte casting slurry; the same method and materials are used to prepare an electrode skeleton casting slurry containing 40% pore-forming agent; a membrane belt casting machine is used to prepare two electrode membranes and an electrolyte casting membrane; hot isostatic pressing is used to form "electrode membrane|electrolyte membrane|electrode membrane" to obtain an integrated skeleton green body; the integrated skeleton green body is sintered, and the sintering process is: heating to 700℃ at 0.5℃ / min and keeping for 2h, heating to 1400℃ at 3℃ / min and keeping for 10h, and then cooling to room temperature at 3℃ / min to obtain the integrated skeleton.

[0089] S2. Preparing a catalyst layer on the inner wall of the porous layer of the integrated skeleton.

[0090] According to the molar ratio of La:Sr:Co:Fe=3:2:1:4, metal nitrates La(NO3)3, Sr(NO3)3, Co(NO3)2, and Fe(NO3)2 were mixed, and then surfactant P123 was added at 10% of the total mass of the added La, Sr, Co, and Fe elements, and a certain amount of water was added to prepare a LSCF oxygen electrode impregnation solution with a concentration of 0.7 mol / L.

[0091] The metal nitrate solutions were mixed according to the molar ratio of Ni:Sm:Ce=5:1:4, and then a surfactant was added according to 10% of the total mass of Ni, Sm, and Ce elements, and a certain amount of water was added to prepare a Ni / SDC fuel electrode impregnation solution with a concentration of 0.7 mol / L.

[0092] The above impregnation solution is absorbed and dripped into the electrode skeleton of the corresponding functional area, and then placed in a muffle furnace for debinding treatment. The above operation is repeated many times until the solution can no longer penetrate, and finally sintering is performed to obtain a complete solid oxide battery. The sintering process is: sintering at a temperature of 900°C for 2h.

[0093] The solid oxide battery prepared in this application has more conductive paths and no cracks are found; through measurement, the open circuit voltage of the prepared solid oxide battery is 0.999V, and the power can reach 579mW·cm -2 .

[0094] Comparative Example 1

[0095] Compared with Example 1, the difference is that in step S1, BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ The average particle size of the powder is 45 nm.

[0096] The open circuit voltage of the prepared solid oxide battery was measured to be 0.850 V, and the power could reach 422 mW·cm -2 .

[0097] Comparative Example 2

[0098] Compared with Example 1, the difference is that in step S1, BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ The average particle size of the powder is 45 nm.

[0099] The open circuit voltage of the prepared solid oxide battery was measured to be 0.848 V, and the power could reach 410 mW·cm -2 .

[0100] Comparative Example 3

[0101] Compared with Example 1, the difference is that in step S1, the average particle size of the GDC powder is 0.08 μm.

[0102] The open circuit voltage of the prepared solid oxide battery was measured to be 0.830 V, and the power could reach 385 mW·cm -2 .

[0103] Comparative Example 4

[0104] Compared with Example 1, the difference is that in step S1, the average particle size of the GDC powder is 0.23 μm.

[0105] The open circuit voltage of the prepared solid oxide battery was measured to be 0.721 V, and the power could reach 320 mW·cm -2 .

[0106] Comparative Example 5

[0107] Compared with Example 1, the difference is that in step S1, BaZr 0.7 Ce 0.2 Y 0.1 O 3-δ The average particle size of the powder was 45 nm, and the average particle size of the GDC powder was 0.23 μm.

[0108] The open circuit voltage of the prepared solid oxide battery was measured to be 0.712 V, and the power could reach 297 mW·cm -2 .

[0109] Comparative Example 6

[0110] Compared with Example 1, the difference is that in step S1, 7% of triethanolamine by weight of the total powder, 3% of dioctyl phthalate by weight of the total powder and 9% of polyethylene glycol by weight of the total powder are added to prepare the electrolyte casting slurry.

[0111] The open circuit voltage of the prepared solid oxide battery was measured to be 0.846 V, and the power could reach 401 mW·cm -2 .

[0112] Comparative Example 7

[0113] Compared with Example 1, the difference is that in step S1, 14% of triethanolamine by weight of the total powder, 3% of dioctyl phthalate by weight of the total powder and 9% of polyethylene glycol by weight of the total powder are added to prepare the electrolyte casting slurry.

[0114] The open circuit voltage of the prepared solid oxide battery was measured to be 0.856 V, and the power could reach 430 mW·cm -2 .

[0115] Comparative Example 8

[0116] Compared with Example 1, the difference is that in step S1, 10% of triethanolamine by weight of the total powder, 2% of dioctyl phthalate by weight of the total powder and 10% of polyethylene glycol by weight of the total powder are added to prepare the electrolyte casting slurry.

[0117] The open circuit voltage of the prepared solid oxide battery was measured to be 0.795 V, and the power could reach 372 mW·cm -2 .

[0118] Comparative Example 9

[0119] Compared with Example 1, the difference is that in step S1, 10% of triethanolamine by weight of the total powder, 5% of dioctyl phthalate by weight of the total powder and 8% of polyethylene glycol by weight of the total powder are added to prepare the electrolyte casting slurry.

[0120] The open circuit voltage of the prepared solid oxide battery was measured to be 0.810 V, and the power could reach 380 mW·cm -2 .

[0121] It can be seen from Example 1 and Comparative Examples 1-5 that the molar ratio and particle size of the proton conductor material and the oxygen ion conductor material have a great influence on the final performance of the product. The reason is that the formation of a non-conductive path leads to a decrease in power and a decrease in open circuit voltage. In addition to the above reasons, the thermal physical properties between the proton conductor material and the oxygen ion conductor material are mismatched and the above factors are superimposed to cause cracks between the two. It can be seen from Example 1 and Comparative Examples 6-9 that the proportion of dispersant, plasticizer and binder added is very critical. Although the three have different functions, they have a certain influence on each other. If there is more dispersant, the dispersion effect is good, and the oxygen ion conductor material and the proton conductor material form a similar amorphous structure, resulting in a decrease in voltage and a decrease in output power. If less dispersant is added, the degree of segregation is aggravated, resulting in an increase in non-conductive paths, thereby reducing the open circuit voltage and reducing the output power.

[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An integrated structure composite conductive solid oxide battery, characterized in that: include: An integrated skeleton, comprising an electrolyte layer and porous layers on both sides, the integrated skeleton is composed of a proton conductor material and an oxygen ion conductor material, the molar ratio of the proton conductor material to the oxygen ion conductor material is 1:(0.8-1.2), and is prepared by mixing and sintering a proton conductor material having an average particle size of 50-60 nm and an oxygen ion conductor material having an average particle size of 0.1-0.2 μm; A catalyst layer is located on the pore walls of the porous layer.

2. The integrated structure composite conductive solid oxide battery according to claim 1, characterized in that: The electrolyte layer and the porous layer use the same proton conductor material and oxygen ion conductor material and the molar ratio of the two is the same.

3. The integrated structure composite conductive solid oxide battery according to claim 1, characterized in that: The proton conductor material includes: BaZr 1-x Y x O 3-δ 、BaZr 1-x Yb x O 3-δ 、BaZr 1-x-y Ce y Y x O 3-δ 、BaZr 1-x-y- z Ce z Y y Yb x O 3-δ One or more of, where 0 <x<1,0<y<1,0<z<1,0<δ<1。 4. The integrated structure composite conductive solid oxide battery according to claim 1, characterized in that: The oxygen ion conductor material includes: Zr x Y y O 2-δ 、Ce x Sm y O 2-δ 、Ce x G y O 2-δ ,La 1-x Sr x Ga 1-y Mg y O 3-δ One or more of, where 0 <x<1,0<y<1,0<δ<1。 5. The method for preparing a solid oxide battery according to any one of claims 1 to 4, characterized in that: preparing an integrated skeleton; A catalyst layer is prepared on the inner wall of the porous layer of the integrated skeleton.

6. The preparation method according to claim 5, characterized in that: The preparation of the integrated skeleton includes: preparing an electrolyte membrane and two electrode membranes; Hot isostatic pressing is used to form "electrode membrane|electrolyte membrane|electrode membrane" to obtain an integrated skeleton green body; The integrated skeleton is sintered to obtain the integrated skeleton.

7. The preparation method according to claim 6, characterized in that: The preparation method of the slurry of the electrolyte membrane and the electrode membrane is: The proton conductor material and the oxygen ion conductor material are weighed and mixed according to a preset ratio, and 8%-13% of the total powder mass of a dispersant, 3%-7% of the total powder mass of a plasticizer and 9%-12% of the total powder mass of a binder are added and mixed evenly to obtain the product.

8. The preparation method according to claim 7, characterized in that: The dispersant is one or more of triethanolamine, sodium polyacrylate and polyoxyethylene; The plasticizer and the binder are one or more of dioctyl phthalate, polyethylene glycol, polyvinyl alcohol and polyvinyl acetate.

9. The preparation method according to claim 6, characterized in that: The hot isostatic pressing process is: maintaining the temperature at 50-85° C. and a pressure of 10-60 MPa for at least 30 minutes.

10. The preparation method according to claim 6, characterized in that: The sintering process is: heating to 650-700°C at a rate of no more than 1°C / min and keeping the temperature for at least 30 minutes, heating to 1200-1600°C at a rate of no more than 3°C / min and keeping the temperature for 2-20 hours, and then cooling to room temperature at a rate of no more than 5°C / min.

Citation Information

Patent Citations

  • A composite solid oxide fuel cell and its preparation method

    CN109921079B

  • A method for preparing a proton-oxygen ion mixed conductor electrolyte, a product thereof, and a battery thereof.

    CN114843569B

  • Preparation method for middle-temperature and low-temperature solid oxide fuel battery

    CN103811788A

  • Compound solid oxide fuel cell and preparation method thereof

    CN109921079A

  • Preparation method of proton-oxygen ion mixed conductor electrolyte, product and battery

    CN114843569A

Cited By

  • Metal oxide capable of conducting oxygen ions and preparation method and application thereof

    CN120463226A

  • A metal oxide capable of conducting oxygen ions and its preparation method and application

    CN120463226B